Bilirubin encephalopathy (kernicterus) in an adult cat. Issue 1 (March 2019) - Saraiva, Luís HG; Andrade, Maria C; Moreira, Matheus VL; Oliveira, Letícia B; Santos, Ágna F; Ferreira, Raquel S; Santos, Willian HM; Ecco, Roselene
Case summary: An adult cat presented with neurological signs and marked icterus. Clinical pathology tests detected increased serum alkaline phosphatase levels, as well as alanine aminotransferase, total bilirubin, unconjugated bilirubin and conjugated bilirubin above the normal reference intervals. Ultrasonography showed hepatomegaly and a dilated gall bladder. Following these results, the cat was referred for a cholecystectomy owing to a clinical suspicion of obstructive cholecystitis. The animal died in the postoperative period and was referred for necropsy. Grossly, the animal had marked icterus. On the cortical surface and in the brain parenchyma there were marked yellowish areas. The liver was diffusely reddish-orange, enlarged and the capsular surface was slightly irregular. The gall bladder was absent. At its anatomical site and surrounding the common hepatic duct, a whitish nodular neoplasia of 2.0 cm was found. Microscopically, a cholangioma was diagnosed in the region of the common hepatic duct. In the white matter of the cerebellar vermis, there was axonal degeneration associated with gliosis. In the Purkinje neuron layer there was slight multifocal necrosis. Some neurons contained amorphous and brownish pigment (bilirubin) in the cytoplasm. Clinical and pathological findings indicated hepatic and post-hepatic icterus from obstructive cholangioma, resulting in kernicterus. Relevance and novel information: Kernicterus is a neurological disorder that is rarely diagnosed in animals, especially in adults. This report provides evidence that kernicterus can occur in adult cats, secondary to increased unconjugated and conjugated bilirubin concentrations.